Shaking hands: priming by social action effects. - Flach, R; Press, C; Badets, A; Heyes, C (2010)
In a semi-naturalistic response-effect compatibility paradigm, participants were given the opportunity to learn that hand-shaking actions would be followed by social effects (human hand-shaking stimuli from a third-person perspective) or inanimate effects (block arrow stimuli). Relative to the actions, these effects appeared on the same or the opposite side of the screen (positional compatibility), and pointed towards or away from the response hand (directional compatibility). After learning, response times indicated a positional compatibility effect for both social and inanimate effects, but a directional compatibility effect occurred only for social action effects. These findings indicate that actions can be represented, not only by their effects on the inanimate world, but also by their effects on the actions of others. They are consistent with ideomotor theory, and with the view that actions are represented by bidirectional response-effect associations. They also have implications with respect to the origins and on-line control of imitation and the systems supporting imitation.